Varovalna bezgavka pri malignem melanomu - Snoj, Marko (Radiology and oncology (Ljubljana), 1999)
The sentinel node biopsy in the patents with malignant melanomais a novel diagnostic procedure which allows to assess the metastatic spread in the lymphatic region by removing only one lymph node. This procedure reduces iatrogenic morbidity. The article gives the description of the procedure and techniques applied. The sentinel node biopsy could become standard treatment method in patients with a melanoma of more than 1 mm in depth.
Keywords: bezgavke; dermatologija; kirurško zdravljenje; Lymph node excision; melanom; Melanoma; Skin neoplasms